Interactions among maize steak virus disease leathopper vector populations and maize cultivars in forest and savanna zones of Nigeria - Asanzi, M.; Bosque Pérez, N.A.; Buddenhagen, I.W.; Gordon, D.; Nault, L. (1994)
Monthly plantings of three maize cultivars with differing resistance/susceptibility to maize streak geminivirus (MSV) and samplings of Cicadulina leafhopper vector were made from December 1988 to April 1990 in the humid forest and from May to November 1989 in the Guinea savanna zones of Nigeria. High MSV disease incidences (43-56%) were recorded on susceptible cultivar TZB-Gusau in late season (July-October) plantings. Hybrid 8321-21 showed significantly lower MSV disease incidence and severity than the other two cultivars, TZB-Gusau and 8329-15. Cicadulina species population peaks (5.2-13.5 leafhoppers/m2) were observed before the rains ended in savanna locations and after the end of the rains in the forest zone. Cicadulina mbila was the predominant species, whereas C.storeyi (syn. C. trangula), C. arachidis, C. similis and C. ghaurii were less common. The proportion of viruliferous leafhoppers increased as the season progressed, reaching maxima of 15-25% at the endof the growing season. Interactions between disease incidence, Cicadulina populations, maize cultivars and rainfall are discussed.